Kinerja Pegawai dan Kualitas Pelayanan Berdasarkan Perspektif Masyarakat Pada Dinas Komunikasi dan Informatika Kota Tasikmalaya - Nutriansyah, Khairiza; Rahwana, Kusuma Agdhi; Fauzy, Depy Muhamad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the influence of Employee Performance and Service Quality on Public Satisfaction at the Tasikmalaya City Communications Office. The method used is a quantitative approach with a causal design and survey techniques. Data were obtained through observation, interviews, questionnaires, and documentation studies. Data analysis was carried out using multiple linear regression with the help of SPSS version 25 software, and supplemented with multiple correlation tests, F tests, T tests, and coefficients of determination. The results of the study revealed that together, Employee Performance and Service Quality have a positive and significant influence on Public Satisfaction. Separately, both Employee Performance and Service Quality were also proven to have a positive and significant influence on Public Satisfaction.